Metformin Attenuates Inflammatory Responses and Enhances Antibody Production in an Acute Pneumonia Model of Streptococcus pneumoniae - Lee, Grace C.; Moreira, Alvaro G.; Hinojosa, Cecilia; Benavides, Raymond; Winter, Caitlyn; Anderson, Audrey C.; Chen, Chang-Jui; Borsa, Noemi; Hastings, Gabrielyd; Black, Cody A.; Bandy, Sarah M.; Shaffer, Alexander; et al. (Frontiers in Aging, 2022)
Metformin may potentially reverse various age-related conditions; however, it is unclear whether metformin can also mitigate or delay the deterioration of immunological resilience that occurs in the context of infections that are commonly observed in older persons. We examined whether metformin promotes the preservation of immunological resilience in an acute S. pneumoniae (SPN) infection challenge in young adult mice. Mice were fed metformin (MET-alone) or standard chow (controls-alone) for 10 weeks prior to receiving intratracheal inoculation of SPN. A subset of each diet group received pneumococcal conjugate vaccine at week 6 (MET + PCV and control + PCV). Compared to controls-alone, MET-alone had significantly less infection-associated morbidity and attenuated inflammatory responses during acute SPN infection. Metformin lowered the expression of genes in the lungs related to inflammation as well as shorter lifespan in humans. This was accompanied by significantly lower levels of pro-inflammatory cytokines (e.g., IL6). MET + PCV vs. control + PCV manifested enhanced SPN anticapsular IgM and IgG levels. The levels of SPN IgM production negatively correlated with expression levels of genes linked to intestinal epithelial structure among MET + PCV vs. control + PCV groups. Correspondingly, the gut microbial composition of metformin-fed mice had a significantly higher abundance in the Verrucomicrobia, Akkermansia muciniphila, a species previously associated with beneficial effects on intestinal integrity and longevity. Together, these findings indicate metformin’s immunoprotective potential to protect against infection-associated declines in immunologic resilience.